Analisis Pola Identifikasi Zero Knowledge Proof Dengan Algoritma Feige Fiat Shamir Menggunakan Blum Blum Shub - Panjaitan, Cherlina Helena Purnamasari; Pangaribuan, Lisda Juliana (MEANS (Media Informasi Analisa dan Sistem), 2021)
Protocol Zero Knowledge Proof is one of the protocols in Cryptography that has a fairly good level of security, because it applies the concept of "Truly Zero Knowledge Proof" which is not leaking any information. This protocol is used in the Fiat Shamir, Guillou Quisquater and Schnorr Feige Algorithms, all of which are Cryptographic Algorithms using private keys and public keys. In the Public key, all three of these Algorithms use a random number generator at the values p and q to get the public key. In this study, the author will generate a public key generation test using CPRNG (Cryptographically-secure Pseudo-Random Number Generator) with the Blum Blum Shub algorithm. The test will be conducted on the Fiat Feige Algorithm, the formation of the key will use the Blum Blum Shub Algorithm, but the Identification Protocol still uses the Fiat Shamir Feige Algorithm. The results of this study show the Feige Fiat Algorithm with the Blum Blum Shub Algorithm as the key builder successfully identifies the pattern sent by the signer.